Cross Diffusion Impacts on Chemically Reactive Unsteady Mass and Energy Transport Over Elongated Surface through Penetrable Medium - Malarselvi, A.; Bhuvaneswari, M.; Sivasankaran, S.; Ganga, B.; K. Abdul Hakeem, A. (International Journal of Engineering and Technology, 2018)
The analysis of Dufour and Soret impacts on chemically reactive unsteady stream with molecules and energy transport in the thin fluid layer over an elongated surface rooted in a penetrable transporting agency with thermal suction/injection is scrutinized. The mathematically formulated PDEs are changed into ODEs with the application of similarity transforms. The converted ODEs are determined by Runge-Kutta method linked shooting process. Numerically computed data are graphically manifested to illustrate the domination of various parametric values. Numerical inspections are made over for local skin drag, rate of energy and solute transport.Â Â